2020
DOI: 10.1186/s12958-020-00648-2
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone alleviates oxidative stress and improves the IVF outcomes of poor ovarian responders: a randomized controlled trial

Abstract: Background: Oxidative stress (OS), defined as an imbalance between excessive reactive oxygen species (ROS) and/ or reactive nitrogen species (RNS) production and antioxidant insufficiency, has been suggested to be involved in the pathogenesis of poor ovarian response (POR). Growth hormone (GH) can reduce OS in some cell types. This study investigated whether GH can improve OS and the in vitro fertilization and embryo transfer (IVF-ET) outcomes of poor ovarian responders. Methods: This study enrolled 105 patien… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…GH is reported to be capable of enhancing the functional mitochondria in oocytes (8), improving the proliferation and differentiation of granulosa cells (9,10) and increasing the endometrial blood perfusion as well (11). In seeking an effective approach to tackle the challenges of POR, GH has been explored in many related studies (8,(12)(13)(14) and utilized clinically for patients with POR during the ovarian stimulation for in vitro fertilization (IVF)/ intracytoplasmic sperm injection (ICSI) as well. Thus, it is crucial to ascertain the validity and specific effects of GH supplementation on the management of patients with POR.…”
Section: Introductionmentioning
confidence: 99%
“…GH is reported to be capable of enhancing the functional mitochondria in oocytes (8), improving the proliferation and differentiation of granulosa cells (9,10) and increasing the endometrial blood perfusion as well (11). In seeking an effective approach to tackle the challenges of POR, GH has been explored in many related studies (8,(12)(13)(14) and utilized clinically for patients with POR during the ovarian stimulation for in vitro fertilization (IVF)/ intracytoplasmic sperm injection (ICSI) as well. Thus, it is crucial to ascertain the validity and specific effects of GH supplementation on the management of patients with POR.…”
Section: Introductionmentioning
confidence: 99%
“…It also corroborates the more recent ndings by Li and Gong in their randomized controlled trials to look at GH use in the setting of history of poor embryo development and poor responder patients respectively. Both studies supported the use of GH in IVF cycles [15,17]. This is contrast to the ndings by Zhu, et al who found that live birth rate was not improved with the use of GH as adjuvant treatment.…”
Section: Discussionmentioning
confidence: 63%
“…Safderin had an arm receive 2.5mg/day as well though this did not start until day 8 and another arm that received 0.1mg/day from cycle day 3 of the previous cycle [18]. Gong et al, administered 4IU/day (1.3mg) starting from Day 4 of the previous cycle [17]. In the LIGHT study, 12 IU/day (4mg) from day of stimulation [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These modules reflected melatonin's effects on endocrine and immune regulation, anti-apoptosis, and ovarian function improvement. In addition, exogenous growth hormone administration has been shown to improve oocyte and embryo quality in IVF treatment of women with poor OR (80,81). The functional modules analysis showed that melatonin is closely related to the synthesis, secretion, and action of GH, which also supports the function of melatonin in improving OR.…”
Section: Important Pathways and Functional Modules Of Melatonin's Putative Targetsmentioning
confidence: 71%